Attribution and health seeking behavior of family members towards Conversion (Dissociative) Disorders - Sawant, S.; Karki, U. (Journal of Psychiatrists' Association of Nepal, 2018)
Introduction: Patients with Conversion (Dissociative) disorders are frequently seen in different communities and hospitals of Nepal. How people attribute illness determines what treatment will be received. Hence this study was conducted to identify attributions and health seeking behavior towards Conversion (Dissociative) disorder.Material and Method: This is a hospital based cross-sectional and exploratory study. Purposive sampling method was used. Duration of study was 6 months from 1st January 2017 to 30th June 2017. Total number of participants was 57. Diagnosis was made using ICD 10 criteria. Self developed questionnaire was used which assessed knowledge and help seeking behavior.Results: The findings showed that the percentage of trance and possession (33.3%) and dissociative convulsions (29.8%) compared to other groups were higher. Illiterate participants were high followed by high school level and intermediate respectively. Among total participants, 47.4% took more than 2 weeks to visit a mental health professional, 31.6% took 48 hours to 2 weeks, and 21.1% visited within 48 hours. Participant’s response to conversion disorder as neither mental illness nor physical illness and response to conversion disorder as mental illness was 43.85%. However response to conversion disorder as a physical illness was 38.6%. Participant’s response to the treatment of conversion disorder for faith healing was higher (52.63%) than to medical and psychosocial treatment (33.33%).Conclusion: Communities in Nepal are still grounded to ethnic practices and faith healing. Conducting awareness program and working in collaboration with faith healers is crucial.